Towards the understanding of the intentionally induced yellow luminescence in GaN nanowires - Rodrigues, J
Gallium nitride (GaN) has gained a lot of attention due to its high range of applications as solid state light emitters and detectors. However, the nitride samples often evidence deep level optically active defects affecting their performance on the high energy spectral region. This is the case for the commonly observed yellow luminescence (YL) band detected in bulk samples and thin films. Despite the large amount of literature reports on the processes that rule this emission in GaN films, there is still some controversy regarding the origin of the defects from where the YL originates. Furthermore, decreasing the dimensionality by analysing GaN nanowires provides new information on the luminescence behaviour when compared with epilayers. By using room temperature optical analysis, we aim to contribute to a deeper insight into the understanding of the YL detected in GaN NW, where YL was induced/enhanced by ion implantation and annealing treatments. YL was seen to be strongly dependent on different surface modifications, the analysis environment and illumination/irradiation excitation time. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.